white anther: A Petunia Mutant That Abolishes Pollen Flavonol Accumulation, Induces Male Sterility, and Is Complemented by a Chalcone Synthase Transgene - Napoli, Carolyn A. (American Society of Plant Physiologists, 1999)
A mutation in an inbred line of petunia (Petunia hybrida) produces a reduction in the deep-purple corolla pigmentation and changes the anther color from yellow to white. In addition, the mutant, designated white anther (wha), is functionally male sterile. The inability of pollen from wha plants to germinate in vitro provides a physiological basis for the lack of seed set observed in self-crosses of the mutant. Biochemical complementation with nanomolar amounts of kaempferol, a flavonol aglycone, confirms that the inability of the wha pollen to germinate is due to a lack of this essential compound. Transgenic complementation with a functional ChsA (Chalcone synthase A) cDNA suggests that the genetic lesion responsible for the wha phenotype is in Chs, the gene for the first enzyme in the flavonol biosynthesis pathway. The genetic background of the parental line, as well as the pollen phenotype, allowed us to deduce that the wha mutation is in ChsA. To our knowledge, wha is the first induced, nontransgenic Chs mutant described in petunia, and analysis of the mutation confirms earlier molecular and genetic observations that only two Chs genes (A and J) are expressed in reproductive tissues and that they are differentially regulated in corolla and anther.